Internet as a supporting tool in English learners and researcher students at Universidad Tecnológica del Chocó - Moreno Mosquera, Francisco (Íkala, Revista de Lenguaje y Cultura, 2005)
This article presents a project carried out in the University of Chocó, to take advantage of the tools offered by the Internet (email, search engines, chat rooms and discussion forums) for formation and research purposes. After being trained in the use of this tools, a group of 10 students went on to teach a virtual English course to beginners, with positive results. Received: 24-03-05/ Accepted: 23-08-05 How to reference this article: Moreno Mosquera, F. (2005). La Internet como herramienta de apoyo en la formación de alumnos investigadores y aprendices del inglés en la Universidad Tecnológica del Chocó. Íkala. 10 (1), pp. 151 – 167